Mineralogy, microfabric and pore evolution in late-middle Ordovician mudstone of the Utica/Point Pleasant sub-basin of Ohio, West Virginia, and Pennsylvania. (December 2021) - Sheets, Julia M.; Welch, Susan A.; Liu, Tingting; Buchwalter, Edwin R.; Swift, Alexander M.; Chipera, Steve; Anovitz, Lawrence M.; Cole, David R.
Abstract: The Utica/Point Pleasant Formations comprise a major unconventional gas resource in the Appalachian Basin. Core samples from several boreholes in Ohio, West Virginia and Pennsylvania were studied to determine mineralogy, microtexture/microfabric, accessible pore surface area, porosity and pore size distribution as a function of maturity in the Utica/Point Pleasant sub-basin. This effort compares shallower, generally more phyllosilicate-rich Utica intervals with deeper, more carbonate-rich Point Pleasant intervals, the latter representative of horizons currently targeted for gas recovery. The Point Pleasant Formation contains mostly calcite (in the form of fossil tests, grains, and cements), distributed within alternating carbonate- and phyllosilicate-rich matrix laminae, as well as coarse-grained fossil-rich laminae. In both Utica and Point Pleasant core samples, the greatest mercury-accessible connected porosity measurements are associated with the highest maturity samples, an observation that is particularly pronounced for the Point Pleasant. More detailed vertical sampling and analysis of core from a well in Harrison County, Ohio (a region that has experienced copious shale gas production) shows that surface area, pore volume and pore connectivity increase locally in target horizons identified for gas recovery. Observations suggest that optimal mixtures and arrangements of minerals and organic matter, as well as increasing maturity, contribute to forming this productive carbonate-rich unconventional resource. In particular, early diagenetic calcite and quartz cement and increasing quantities of silt-sized particles are associated with higher measured connected porosities, while later-stage matrix dolomitization and recrystallization of fossil laminae tend to occlude the pore network. Highlights: Preservation of matrix laminae suggests rapid cementation during early diagenesis. Clay- and silt-sized mineral-OM pockets contribute greatly to connected porosity. Calcite and quartz as silt-sized grains and cements preserve matrix porosity. Dolomitization of matrix laminae occludes pores in the mudrock microfabric. Connected porosity and specific surface area are greatest for high Ro samples.